2020
DOI: 10.14336/ad.2019.0923
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Deficits in Neurodegenerative Disorders: Uncovering Molecular Mechanisms to Drive Innovative Therapeutic Development

Abstract: Cell cycle dysregulation has been implicated in the pathogenesis of neurodegenerative disorders. Specialised function obligates neuronal cells to subsist in a quiescent state of cell cycle once differentiated and therefore the circumstances and mechanisms underlying aberrant cell cycle activation in post-mitotic neurons in physiological and disease conditions remains an intriguing area of research. There is a strict requirement of concurrence to cell cycle regulation for neurons to ensure intracellular biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 210 publications
(232 reference statements)
1
42
0
Order By: Relevance
“…After neurons were exposed to oxidative stress, the expression of cell cycle markers was up‐regulated(Schwartz et al., 2007). When the neuron cell cycle reactivation, it may cause cell apoptosis (Joseph et al., 2020). (Frade & Ovejero‐Benito, 2015)Aberrant activation of cell cycle and abnormal expression of mitotic related proteins in the substantia nigra (SN) were found in PD autopsy tissues(Jordan‐Sciutto et al., 2003) and mice model (Smith et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After neurons were exposed to oxidative stress, the expression of cell cycle markers was up‐regulated(Schwartz et al., 2007). When the neuron cell cycle reactivation, it may cause cell apoptosis (Joseph et al., 2020). (Frade & Ovejero‐Benito, 2015)Aberrant activation of cell cycle and abnormal expression of mitotic related proteins in the substantia nigra (SN) were found in PD autopsy tissues(Jordan‐Sciutto et al., 2003) and mice model (Smith et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…During S phase, the cyclin A/Cdk1 complex activates late replication origins. Finally, G2/M transition is regulated by the formation of the Cdk1/cyclin B complex, which helps cells enter the M phase (Joseph et al, 2020). The western blotting results showed that MPP + increased the expression of cyclinD1, CyclinE1, CDK2 and cyclinA2 in SH-SY5Y cells.…”
mentioning
confidence: 95%
“…Different mechanisms have been implicated in the progression and pathogenesis of NDs, including OS, neuroinflammation, apoptosis, excitotoxicity, and mitochondrial dysfunction [ 43 , 44 , 45 , 46 , 47 ] ( Figure 1 ).…”
Section: Mechanisms Involved In Neurodegenerationmentioning
confidence: 99%
“…Extrinsic and intrinsic pathways consist of death receptor activation upon ligand binding and production of pro-apoptotic factors in cytosol, respectively. Subsequently, the intrinsic pathway triggers caspase-independent apoptosis or caspase-dependent apoptosis [ 46 , 48 ]. Characterized by chromatin condensation, cell shrinkage, membrane cell death, and DNA fragmentation, neuronal apoptosis is the neuropathological hallmark of NDs.…”
Section: Mechanisms Involved In Neurodegenerationmentioning
confidence: 99%
“…Although neurons are post-mitotic, cell cycle re-entry can occur following defective DNA repair. In fact, re-initiation and dysregulation of the cell cycle is a recognized feature of neurodegenerative disorders, 119 , 120 where dysregulation can occur from various stressors, such as excitotoxicity, oxidative stress and DNA damage. 121 This process can induce senescence or apoptosis depending on the extent of cell cycle progression and the amount of DNA damage present.…”
Section: Breast Cancer Typementioning
confidence: 99%